Reduction in extrathyroidal triiodothyronine production by propylthiouracil in man. - Saberi, M (1975)
To determine if propylthiouracil (PTU) inhibited extrathyroidal thyroxine (T4) to triiodothyronine (T3) conversion in man, PTU was administered to T4-treated hypothyroid patients and serial measurements of T4, T3, and thyrotropin (TSH) carried out. All patients had proven thyroidal hypothyroidism and had been receiving 0.1 or 0.2 mg T4 daily for at least 2 mo before study. Hormone measurements were made for 5 consecutive days before and daily during a 7-day treatment period with PTU, 1,000 mg/day. In eight patients receiving 0.1 mg T4 daily, administration of PTU resulted in a prompt fall in mean serum T3 concentrations from 78 plus or minus 6 ng/100 ml (SEM) to 61 plus or minus 3 ng/100 ml after 1 day. The mean serum T3 concentrations ranged from 55 to 60 ng/100 ml during the remainder of the PTU treatment period (P less than 0.01). The mean control serum TSH concentration was 29.6 muU/ml and it increased to a peak of 40 muU/ml on the 5th and 6th days. In five patients receiving 0.2 mg T4 daily, the mean control serum T3 concentration was 84 plus or minus 7 NG/100ML. It fell to 70 plus or minus 5 ng/100 ml after 1 day and 63 plus or minus 7 ng/100 ml after 2 days of PTU administration and thereafter ranged from 6) to 69 ng/100 ml (P LESS THAN 0.01). Serum TSH concentrations did not increase. No changes in serum T4 concentrations were found in either group. In five patients who received 100 mg methimazole (MMI) daily for 7 days there were no changes in serum T4, T3, or TSH concentrations. These results indicate that PTU, but not MMI, produces a prompt and sustained, albeit modest, reduction in serum T3 concentrations in patients whose sole or major source of T3 is ingested T4. These findings most likely result from inhibition of extrathyroidal formation of T3 from T4.